Evaluating the change process of a brief cognitive behavior therapy workshop for psychological distress among primary care self-referrals in Selangor, Malaysia - Sam, Jeng Mun; Siti Irma Fadhilah Ismail, Siti Irma Fadhilah; Tan, Kit Aun; Mohd Sidik, Sherina; Jamil Osman, Zubaidah (Frontiers Research Foundation, 2022)
Despite the high prevalence of psychological distress in primary care, only a limited number of individuals can benefit from early and evidenced-based psychological approach. Barriers to help-seeking attributable to stigma, lack of proper care pathway to evidence-based psychological interventions, and a high volume of primary care attendees are among the factors that contribute to the inadequate psychological treatments. This study examined the implementation of a change process using a brief cognitive behavioral therapy (b-CBT) workshop as a potential approach in managing psychological distress among 73 primary care self-referrals using purposive sampling. One-way repeated-measures multivariate analysis of variance (ANOVA) was used to analyze changes in psychological distress within a non-randomized quasi-experimental study. Results revealed significant differences in psychological distress using Depression, Anxiety, and Stress Scale-21 items at three time points (pre-intervention, post-intervention, and 1-month follow-up). Implementation of the b-CBT workshop showed positive changes for psychological distress, suggesting the possibility of integrating brief, non-stigmatized, and evidence-based psychological approach at the primary care level. However, the self-referral characteristics of the attendees remain unknown. Factors such as potential feasibility, participant's usability and satisfaction, and implementation of b-CBT workshop to improve psychological distress are discussed in this study.